Development and Validation of Perceived Oral Health Benefits on Yoga Scale (POBYS) - Balkrishna, Acharya; Singh, Kuldeep; Sharma, Abhishek; Karthikeyan, Nagarajan; Gowda, Paran (Brazilian Dental Science, 2021)
Objective: Sustained practice of Yoga leads to self-awareness, physical strength and high sense of energy. Yoga stimulates antioxidant levels in the body and reduces likelihood of dental disorders. No research has been undertaken connecting perception on yoga and oral health behaviors. The present study is an attempt to develop a psychometric scale entitled Perceived Benefits on Yoga Scale (PBYS) to measure individuals’ perception on Yoga in relation to oral health behaviors. Material and methods: The psychometric tool was developed based on the concepts of Health Benefit Model (HBM). Among the four components of the model, the present study considered “perceived benefits” component. A total of 206 individuals participated in the study. To analyze the scale theoretically, face and content validity were assessed. Reliability of the scale was tested using Cronbach’s alpha and Spearman-Brown coefficient. Using exploratory and confirmatory factor analysis, construct validity was tested. Cronbach alpha and Spearman- Brown coefficient were applied to test the reliability of scale. Results: There were six items in the final scale, with a Spearman- Brown coefficient of 0.92 and Cronbach’s alpha of 0.91. Statistically significant (p < 0.001) positive correlation was found between POBYS scores and Yoga Self-Efficacy Scale (YSES). Validity of scale is within accepted range as indicated by Goodness of Fit indices. Conclusion: POBYS is a reliable and valid measure of perception on yoga outcomes with specific reference to oral health behavior. Keywords Yoga; Health belief model; Oral health behavior; Scale development; Confirmatory factor analysis.